Reputation: 65
So at the end of my truth table I got:
NOT NOT ABC.NOT ABD
________
___ ___
ABC.ABD
Does this simplify into ABC+ABD? Also what laws would I use?
Upvotes: 0
Views: 62
Reputation: 2103
For a start I don't like the way they teach binary simplification. To make things much easier for yourself take these rules instead of the ones they taught you:
You can work out xor and etc.. yourself using these.
Now then using these rules:
NOT(NOT(A AND B AND C) AND (NOT (A AND B AND D)))
= 1 - ((1 - ABC)*(1 - ABD))
= 1 - (1 - ABC)(1 - ABD)
= 1 - 1 + ABD + ABC - ABCABD
= ABD + ABC - ABCD
= AB(D + C - CD)
= A AND B AND (C OR D)
which is equivalant to ABC + ABD using your system.
Edit: First 3 equals (but a bit slower):
NOT(NOT(A AND B AND C) AND (NOT (A AND B AND D)))
->
NOT((NOT(ABC)) AND (NOT (ABD)))
->
1 - ((NOT(ABC))(NOT(ABD)))
->
1 - (1 - ABC)(1 - ABC)
-> expanding the brackets
1 - (1 * 1 - ABC * 1 - ABD * 1 + ABC * ABD)
->
1 - (1 - ABC - ABD + ABCABD)
-> multiple out the bracket
1 - 1 + ABD + ABC - ABCABD
glad I could help ^^
Upvotes: 1